Stakeholder Mapping, Social Network and Multi-Stakeholder Strategies Analysis in Mali’s Small Ruminant Value Chain, Plus a Dive into Multi-Stakeholder Innovation Platforms as a Form & Driver of Inclusive SAPLING Innovation Packages - Idoudi, Zied; Ahmadou, Sow; Rudiger, Udo; Sacko, Idrissa; Dione, Michel; Rekik, Mourad (International Center for Agricultural Research in the Dry Areas, 2023)
Within the framework of the CGIAR 2030 Research and Innovation Strategy, CGIAR is actively engaged in a series of initiatives aimed at realizing a world with sustainable and resilient food, land, and water systems. These initiatives have the overarching goal of fostering more diverse, healthy, safe, sufficient, and affordable diets while ensuring improved livelihoods and greater social equality, all while operating within global and regional environmental boundaries. One of these significant initiatives is the CGIAR SAPLING (Sustainable Animal Productivity for Livelihoods, Nutrition, and Gender Inclusion) Initiative. Led by the International Livestock Research Institute (ILRI) the International Center for Agricultural Research in the Dry Areas (ICARDA) and the Alliance of Bioversity International & CIAT, SAPLING focuses on empowering small ruminant, dairy, and poultry producers, with an emphasis on women and young individuals—, by involving them in inclusive value chains and helping them achieve sustainable productivity gains of up to 30- 50%, ultimately enhancing their livelihoods. In Mali, SAPLING is committed to transforming the small ruminant value chain. This transformation is to be achieved through the development and widespread adoption of inclusive innovation packages that encompass aspects such as health, nutrition, reproduction, capacity building, and market access. The initiative offers a wide range of innovation packages, incorporating both technological and institutional innovations. To effectively implement and sustain these innovations, it is essential to identify key stakeholders who can contribute at various levels and scales to achieve the initiative's outcomes in Mali. To address this need, three workshops were conducted in Mali, specifically in Bamako, Sikasso, and Ségou, on July 7, 10, and 13, 2023, respectively. These workshops were dedicated to activities such as stakeholder mapping, social network analysis, and multi-stakeholder strategy analysis within Mali's small ruminant value chain. Additionally, they delved into the concept of Multi-Stakeholder Innovation Platform (MSIP) as a means to drive inclusive SAPLING innovation packages in Mali. MSIPs have been established in four communes of Sikasso by previous program namely the Feed the Future Mali Livestock Scaling Technology Program to foster the transformation of livestock value chains through the development of partnerships among key stakeholders. MSIPs are seen as a mechanism to harness collective action to address the constraints and opportunities pertaining to ruminant livestock value chains development. In this specific context, they have been established to empower livestock value chain stakeholders to scale up innovative solutions to sectoral challenges. Therefore, MSIPs are continued under SAPLING, with more focus on small ruminants’ value chains to transforming food security and nutrition with more focus on women and youth in the project areas.